Optimizing Da'wah in the Digital Era Through the Imam, Dai, and Khatib Certification Program in Bandar Lampung City - Nurkholis, Nurkholis; Noor, Marzuki (West Science Islamic Studies, 2025)
digital era provides significant opportunities for the development of Islamic preaching (dakwah) through information technology. However, challenges to the competence and capabilities of imams, preachers (dai), and khatibs have also intensified. This study aims to explore the implementation of the certification program for Imams, Dai, and Khatibs in Bandar Lampung City as an effort to optimize dakwah in the digital era. Using a descriptive qualitative approach, the study's findings indicate that this certification program not only enhances competence in delivering digital-based dakwah but also promotes professionalism in preaching. Technological support, government regulations, and collaboration with the community are key factors contributing to the success of this program.